2013
DOI: 10.1063/1.4797459
|View full text |Cite
|
Sign up to set email alerts
|

An alternate approach to the production of radioisotopes for nuclear medicine applications

Abstract: There is a growing need for the production of radioisotopes for both diagnostic and therapeutic medical applications. Radioisotopes that are produced using the (n,γ) or (γ,n) reactions, however, typically result in samples with low specific activity (radioactivity∕gram) due to the high abundance of target material of the same element. One method to effectively remove the isotopic impurity is electro-magnetic mass separation. An Ion Source Test Facility has been constructed at TRIUMF to develop high-intensity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It is, therefore, interesting to contemplate the possibility of using EM isotope separation as the technology of choice to remove isotopic impurities. Recently, Lapi et al [24] and D'Auria et al [25] demonstrated efficient EM isotope separation for 99 Mo. These authors also speculated about using EM isotope separation for many other medically important radionuclides, some of which can be produced in sufficient quantities via reactions such (n,γ) and (γ,n) but which result in products with a low specific activity.…”
Section: Electromagnetic Isotope Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, therefore, interesting to contemplate the possibility of using EM isotope separation as the technology of choice to remove isotopic impurities. Recently, Lapi et al [24] and D'Auria et al [25] demonstrated efficient EM isotope separation for 99 Mo. These authors also speculated about using EM isotope separation for many other medically important radionuclides, some of which can be produced in sufficient quantities via reactions such (n,γ) and (γ,n) but which result in products with a low specific activity.…”
Section: Electromagnetic Isotope Separationmentioning
confidence: 99%
“…in the case of 18 F. Furthermore, future dedicated facilities may be small and compact, in stark contrast to the large spallation + ISOL facilities such as ISOLDE at CERN. A possible scenario may include a commercial 70 MeV cyclotron, such as the IBA Cyclone 70 XP, Best BSCI 70p or CIAE CYCCIAE70 [7] in conjunction with a compact EM isotope separator, such as that of the Ion Source Test Facility (ISTF) at TRIUMF [25]. This last-mentioned facility is a fantastic step in the right direction and may be ideally suited for proofof-principle studies.…”
Section: Electromagnetic Isotope Separationmentioning
confidence: 99%
“…Currently, most HEU used in isotope production is enriched to greater than 90% (3). The United States produces 93% of the HEU that is used in the world for the production of 99 Mo.…”
Section: Historical 99 Mo Productionmentioning
confidence: 99%